2016
DOI: 10.1371/journal.pone.0149871
|View full text |Cite
|
Sign up to set email alerts
|

A Single 17D Yellow Fever Vaccination Provides Lifelong Immunity; Characterization of Yellow-Fever-Specific Neutralizing Antibody and T-Cell Responses after Vaccination

Abstract: IntroductionPrompted by recent amendments of Yellow Fever (YF) vaccination guidelines from boost to single vaccination strategy and the paucity of clinical data to support this adjustment, we used the profile of the YF-specific CD8+ T-cell subset profiles after primary vaccination and neutralizing antibodies as a proxy for potentially longer lasting immunity.Methods and FindingsPBMCs and serum were collected in six individuals on days 0, 3, 5, 12, 28 and 180, and in 99 individuals >10 years after YF-vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 62 publications
5
82
0
1
Order By: Relevance
“…The response to a single immunodominant epitope can contribute to up to 60% of the total response It was previously shown that in HLA-A02 donors the NS4B 214−222 LLWNGPMAV immunodominant epitope elicits the strongest CD8+ T-cell response [3,5,7,15]. Using an HLA-A02-pMHC-dextramer, we isolated NS4Bspecific CD8+ T-cells from both donors ( Fig.…”
Section: Tcr Sequencing Shows the Transition Of Clonotypes Between Mementioning
confidence: 98%
See 1 more Smart Citation
“…The response to a single immunodominant epitope can contribute to up to 60% of the total response It was previously shown that in HLA-A02 donors the NS4B 214−222 LLWNGPMAV immunodominant epitope elicits the strongest CD8+ T-cell response [3,5,7,15]. Using an HLA-A02-pMHC-dextramer, we isolated NS4Bspecific CD8+ T-cells from both donors ( Fig.…”
Section: Tcr Sequencing Shows the Transition Of Clonotypes Between Mementioning
confidence: 98%
“…An essential feature of effective vaccination is the formation of immune memory. Although most of the effector cells die shortly after viral clearance, YF-specific T-cells could be found in the blood of vaccinated individuals years [3,7,8,11] and even decades after vaccination [14,15]. While the immune response to the primary vaccination has been much studied, there is only limited data on the response to the booster vaccination with YFV17D.…”
Section: Introductionmentioning
confidence: 99%
“…Increased CD8 þ T cell proliferation correlates directly with the levels of virus genomes in plasma, which peaks once virus is eliminated . CD8 þ T cell clones responding to 17D differentiate into central memory and effector memory subpopulations (Dewitt et al, 2015) and are still detectable 25 years following vaccination (Wieten et al, 2016). 17D-specific CD8 þ T cells respond to epitopes contained from every protein product generated by the 17D polyprotein, and upon peptide restimulation, these 17D-specific CD8 þ T cells have activated cytotoxic profiles including increased expression of IFN-g, TNF-a, and MIP1-b and IL-2 granzyme B and CD107a (Blom et al, 2013;Akondy et al, 2009) but are not exhausted and retain long-lived memory and polyfunctional phenotypes for at least 2 years following 17D rechallenge (Akondy et al, 2009).…”
Section: Flavivirus Classification Epidemiology Immunology and Vacmentioning
confidence: 99%
“…One of the most important genome loci involved in immunity to pathogens is the major histocompatibility complex (MHC). This region encodes the classical MHC-I and MHC-II genes as well as non-classical MHC genes such as MHC-E, which has received much recent attention (Davis et al, 2016; Hansen et al, 2016; Pietra et al, 2010; van Meijgaarden et al, 2015) and others. It also contains genes that encode proteins involved in a number of other immunological processes, such as the Transporter associated with Antigen Processing (TAP) and Tumor Necrosis Factor alpha (TNF-α) (Horton et al, 2004; Shiina et al, 2009).…”
mentioning
confidence: 99%
“…The ultimate goal of vaccines in general is to prevent infection at the port of entry, suggesting that neutralizing antibodies should be the most critical immunological component of a vaccine. However, one of the most effective vaccines ever created, the Yellow Fever vaccine 17D, induces a broad immunological response that includes antibodies and TCD8+ cells (Muyanja et al, 2014; Querec et al, 2009; Wieten et al, 2016), all of which likely contribute to viral prevention and clearance. In addition, a number of vaccines could be enhanced by induction of effective TCD8+ cells, which can target all viral proteins, rather than just the envelope glycoprotein, the predominant target of neutralizing antibodies.…”
mentioning
confidence: 99%